2019
DOI: 10.1016/j.chb.2017.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Using educational data from teaching and learning to inform teachers’ reflective educational design in inquiry-based STEM education

Abstract: Highlights • Tool-supported Guidance is essential for effective Inquiry-based education • Teaching and Learning Analytics (TLA) can support teachers provide appropriate Guidance • The TLA method and supporting tool provides analyses of the level of Guidance in Inquiry-based scenarios • Analyses of the design can be investigated against customizable learners' data and profiles • Insights from these combined analyses could help teachers improve their teaching designs Abstract: Science, Technology, Engineering an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 45 publications
1
28
0
1
Order By: Relevance
“…The global theme of "subject integration/project-based learning/design-based education" was found documents mentioned about integrated STEM education, the creation of integrated STEM, the implementation of integrated STEM, and the assessment of integrated STEM. This global theme was related to other global theme including assessment, professional development, willingness, and STEM content, aspects previously described in literature (Pitt, 2009;Sergis, 2019). The relationship between the "subject integration/project-based learning/design-based education" global theme and assessment can be found in the words in the documents.…”
Section: Global Theme 1: Subject Integration/project-based Learning/dmentioning
confidence: 66%
See 1 more Smart Citation
“…The global theme of "subject integration/project-based learning/design-based education" was found documents mentioned about integrated STEM education, the creation of integrated STEM, the implementation of integrated STEM, and the assessment of integrated STEM. This global theme was related to other global theme including assessment, professional development, willingness, and STEM content, aspects previously described in literature (Pitt, 2009;Sergis, 2019). The relationship between the "subject integration/project-based learning/design-based education" global theme and assessment can be found in the words in the documents.…”
Section: Global Theme 1: Subject Integration/project-based Learning/dmentioning
confidence: 66%
“…Science, Technology, Engineering, and Mathematics (STEM) education has become the topic of much debate in educational settings over the past several decades (Herschbach, 2011;Sergis et al 2019). Another cause for changes in STEM education is the difference in the way today"s students are motivated (Chittum et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Notable examples in this area that relate to our work include Sergis et al . () that investigate how to support teacher guidance and reflection during inquiry tasks, Martinez‐Maldonado et al . () that aimed explicitly to enhance teacher awareness of small group work with interactive surfaces, and van Leeuwen () where teachers regulated collaborating groups in simulation situations.…”
Section: Background and Related Workmentioning
confidence: 99%
“…This focus on orchestration creates a high synergetic potential between the work reported here and the use of LA tools in Computer-Supported Collaborative Learning (CSCL) and Inquiry-based learning (IBL) approaches. Notable examples in this area that relate to our work include Sergis et al (2019) that investigate how to support teacher guidance and reflection during inquiry tasks, Martinez-Maldonado et al (2015) that aimed explicitly to enhance teacher awareness of small group work with interactive surfaces, and van Leeuwen (2015) where teachers regulated collaborating groups in simulation situations. For a review in the broader area of natural user interfaces see Martinez-Maldonado et al (2017).…”
Section: Related Workmentioning
confidence: 99%
“…The lecturer should give feedbacks to strengthen the use of the strategy (Juwah et al, 2004;Sutton et al, 2010;Wiliam, 2013;) and correct or conduct remedial teaching if the implemented strategy was inappropriate or out of what has been expected (Luoch, 2016;Oyekan, 2013). OECD (2016) suggested that an excellent cognitive teaching strategy should at least (1) expect students to explain their thinking on complex problems; (2) encourage students to solve problems in more than one way; (3) require students to provide written explanations of how they the Sergis et al, 2019;Shaikh & Khoja, 2012;Whitaker, 2017). One of the most familiar learning tools is a lesson plan, which comprises identity, goals, materials, learning procedures, learning sources, and assessment (Cherasaro et al, 2015;De Witte et al, 2015;Surgenor, 2010).…”
Section: Skills In Constructing Biology Learning Toolsmentioning
confidence: 99%